(untitled) (LIS TODAY, 2023)
The present study has measured the use and satisfaction of library resources and services by the teachers and students of four colleges of Lunglei districts of Mizoram. The colleges are Lunglei Government College, Government J. Buana College, Government Hnahthial College, and Higher and Technical Institute Mizoram (HATIM. The study is survey based with the help of purposive sampling techniques. The total sample size is 240. The findings revealed that majority of respondents are satisfied with textbook, reference collections, circulation and reprographic service while nearly the whole respondent shows their Un-satisfaction with the collection of e-resources and journal collection. Circulation and reprography services of the library were more satisfactory to its users. Among the colleges, highest satisfaction was observed in HATIM College.